New EU countries and euro adoption - Cherniavska, Anna (2020)
This thesis is oriented on the analysis of the effects of the adoption of the Euro by the new European countries, and whether the rest of them should adopt the common currency. The thesis aims to explore whether the adoption of the Euro brought positive changes to the economies of the chosen countries both in the short and long-term periods. To reach the goal, both qualitative – analysis of changes within the chosen economic indicators; and quantitative – beta convergence; analyses were used in the thesis.